Power, Control, and an Interplanetary Dialectic of Masculinities in Ursula K. Le Guin's The Dispossessed. Issue 3 (December 2019) - Pitts, Michael
Abstract : This paper explores the intersection of masculinities and feminist science fiction of the 1970s, specifically Ursula K. Le Guin's The Dispossessed (1974). It argues that the work of Le Guin and other contemporary writers contains portrayals of alternative masculinities that stand in stark contrast to those of earlier science fiction. These renderings of more egalitarian conceptions of manhood, while often overlooked in favor of analyses of the female characters populating these novels, reveal important links connecting masculinities and the nation and augur the possibilities for science fiction to imagine new, healthier conceptions of maleness.